Effect of Foreign Banking Capital on the Financial Innovativeness of the Country: Evidence from Former Soviet Union and Young EU Members Countries - F. F. Murshudli (Финансы: теория и практика, 2022)
The main hypothesis of the paper was the assumption that the increase in the level of innovation of the financial sector in the post-Soviet states and young European Union (EU) members with an imperfect banking sector and a protracted financial crisis is accompanied by difficulties accessing financing sources and significantly depends on the volume foreign banking capital. The aim of the study is to identify the correlation between the growth of financial innovativeness of the country and the level of foreign banking capital, using Panel data analysis from 2009 to 2019. Unlike previous studies, it was taken into account that the level of financial innovation of the republics of the former Soviet Union is increasingly dependent on external credit resources, while the innovative development of the EU countries becomes financially independent, and this constitutes the scientific novelty of the research. The results confirm the relationship between foreign banking capital and the growth of financial innovativeness of the country, especially with its low and medium levels. To test his hypothesis, the author presented empirical models with the conditions of interaction with the Financial Innovativeness Index. Based on a comparison of indicators of the financial innovation of the country and foreign banking capital, clusters of countries are distinguished according to the nature and direction of the relationship of the analyzed indicators. The author concludes that the increase in the level of innovation in the financial sector of the countries of the former Soviet Union and young EU members depends on the amount of foreign banking capital and the need to consistently expand the tools for the country’s economic growth by attracting it.